The religious worldviews reflected in the Dead Sea Scrolls: proceedings of the fourteenth international symposium of the Orion Center for the Study of the Dead Sea Scrolls and Associated Literature, 28-30 May, 2013 - Clements, Ruth E.; Ḳisṭer, Menaḥem; Segal, Michael; Clements, Ruth (Studies on the texts of the desert of Judah, 2018)
Intro -- Contents -- Preface -- Abbreviations -- Contributors -- An Investigation into the Continuity between Biblical Literature and the Scrolls -- Theologies in Tension in the Dead Sea Scrolls -- Concealing and Revealing in the Ideology of the Qumran Community -- Between Divine Justice and Doxology: Images of Heaven in the Dead Sea Scrolls -- The Notion of the Spirit in the Dead Sea Scrolls and in Texts of the Early Jesus Movement -- Qumran, Jubilees, and the Jewish Dimensions of 2 Corinthians 6:14-7:1 -- The Divine Name in the Dead Sea Scrolls and in New Testament Writings -- God, Gods, and Godhead in the Songs of the Sabbath Sacrifice -- Predeterminism and Moral Agency in the Hodayot -- Interpreting History in Qumran Texts -- Eschatology and the Sacred Past in Serekh ha-Milḥamah -- Two Creations for One Nation: Apocalyptic Worldviews in Jubilees and Qumran Writings -- Index of Modern Authors -- Index of Ancient Sources